2003
DOI: 10.1002/yea.1020
|View full text |Cite
|
Sign up to set email alerts
|

Non‐AUG translation initiation of mRNA encoding acidic ribosomal P2A protein in Candida albicans

Abstract: The eukaryotic 60S ribosomal subunit has a set of very acidic proteins (P-proteins), which form a distinct lateral protuberance called the stalk structure. This protein complex is directly involved in the elongation step of polypeptide synthesis. In our study on acidic ribosomal P-proteins from the human opportunistic pathogen Candida albicans, we isolated and characterized one of the genes, called CARP2A, and its product, the P2A protein. The CARP2A gene is intron-less, present in a single copy per haploid ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Complementary to our viewpoint, an interesting report published very recently argued that a GUG codon may serve as the exclusive translation initiator for the gene encoding acidic ribosomal P2A protein in the yeast Candida albicans (36). In addition, preliminary screening of genomic sequences for GlyRS genes in other low eukaryotes revealed the presence of only one such gene in both C. albicans and Schizosaccharomyces pombe, and even more incredibly, only one suitable AUG triplet in each of the two genes.…”
Section: Discussionsupporting
confidence: 59%
“…Complementary to our viewpoint, an interesting report published very recently argued that a GUG codon may serve as the exclusive translation initiator for the gene encoding acidic ribosomal P2A protein in the yeast Candida albicans (36). In addition, preliminary screening of genomic sequences for GlyRS genes in other low eukaryotes revealed the presence of only one such gene in both C. albicans and Schizosaccharomyces pombe, and even more incredibly, only one suitable AUG triplet in each of the two genes.…”
Section: Discussionsupporting
confidence: 59%
“…Contrary to what happens in prokaryotes, initiation at GUG codons occurs rarely in higher eukaryotes (2). In fungi, a GUG start codon has been demonstrated for the C. albicans ribosomal protein P2A (8) and has also been proposed for other genes based on amino acid comparison of similar proteins, as is the case with ACV (␣-aminoadipyl-cysteinyl-valine) synthetase of Cephalosporium acremonium (32). In vitro experiments have also demonstrated that the Aspergillus nidulans areB gene may use a GUG codon as a minor initiation site (33).…”
Section: Discussionmentioning
confidence: 90%
“…So far, only three yeast genes have been demonstrated to initiate at native non-AUG codons: the Candida albicans gene coding for the acidic ribosomal protein P2A (CARP2A gene) (8) and the Saccharomyces cerevisiae genes GRS1 and ALA1, which code for glycyl-tRNA synthetase (GlyRS) and alanyl-tRNA synthetase (AlaRS), respectively (9,10). The GRS1 and ALA1 genes provide both the cytoplasmic and mitochondrial isoforms of the corresponding enzymes, the mitochondrial forms being initiated from non-AUG triplets upstream of the AUG initiators of the cytoplasmic counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps for that reason, yeast cannot efficiently use non-AUG codons as the translation start site (23,24). Nonetheless, three yeast genes, GRS1 (one of the two glycyl-tRNA synthetase (GlyRS) genes in S. cerevisiae) (11), ALA1 (the only alanyl-tRNA synthetase (AlaRS) gene in S. cerevisiae) (12), and CARP2A (the gene coding for acidic ribosomal protein P2A in Candida albicans) (25), have recently been reported to use naturally occurring non-AUG triplets as translation initiators. Moreover, a very recent study suggested that the translational efficiency of non-AUG initiation codons is significantly affected (up to 32-fold) by nucleotides at its relative Ϫ3 to Ϫ1 position, and, to a lesser extent, ϩ4 (26).…”
mentioning
confidence: 99%